Introduction to classical and quantum harmonic oscillators - Bloch, S.C. (Sylvan Charles) (John Wiley & Sons, 1997)
"Complete with disk, Introduction to Classical and Quantum Harmonics Oscillators is a hands-on guide to understanding how harmonic oscillators function and the analytical systems used to describe them. Professionals and students in electrical engineering, mechanical engineering, physics, and chemistry will gain insight in applying these analytical techniques to even more complex systems. With the help of spreadsheets ready to run on Microsoft Excel (or easily imported to Quattro Pro or Lotus 1-2-3) users will be able to thoroughly and easily examine concepts and questions of considerable difficulty and breadth, without painstaking calculation." "The software allows users to imagine, speculate, and ask "what if ...?" and then instantly see the answer. You're not only able to instantly visualize results but also to interface with data acquisition boards to import real-world information. The graphic capability of the software allows you to view your work in color and watch new results blossom as you change parameters and initial conditions."--BOOK JACKET.